The spice for joint inflammation: anti-inflammatory role of curcumin in treating osteoarthritis - Chin KY (Dove Medical Press, 2016)
Kok-Yong Chin Department of Pharmacology, Universiti Kebangsaan Malaysia Medical Centre, Cheras, Malaysia Abstract: Osteoarthritis is a degenerative disease of the joint affecting aging populations worldwide. It has an underlying inflammatory cause, which contributes to the loss of chondrocytes, leading to diminished cartilage layer at the affected joints. Compounds with anti-inflammatory properties are potential treatment agents for osteoarthritis. Curcumin derived from Curcuma species is an anti-inflammatory compound as such. This review aims to summarize the antiosteoarthritic effects of curcumin derived from clinical and preclinical studies. Many clinical trials have been conducted to determine the effectiveness of curcumin in osteoarthritic patients. Extracts of Curcuma species, curcuminoids and enhanced curcumin, were used in these studies. Patients with osteoarthritis showed improvement in pain, physical function, and quality of life after taking curcumin. They also reported reduced concomitant usage of analgesics and side effects during treatment. In vitro studies demonstrated that curcumin could prevent the apoptosis of chondrocytes, suppress the release of proteoglycans and metal metalloproteases and expression of cyclooxygenase, prostaglandin E-2, and inflammatory cytokines in chondrocytes. These were achieved by blocking the activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) system in the chondrocytes, by preventing the activation of nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha, phosphorylation, and translocation of the p65 subunit of NF-κB complexes into the nucleus. In conclusion, curcumin is a potential candidate for the treatment of osteoarthritis. More well-planned randomized control trials and enhanced curcumin formulation are required to justify the use of curcumin in treating osteoarthritis. Keywords: cartilage, chondrocyte, Curcuma, inflammation, joint, pain